Students’ Understanding and Learning: Mediation Effects of Cognitive Engagement in Online Classes (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Beneath the perils of pandemic, this trend has moved very fast and in a professional manner to fill in the space produced as a result of suspended classroom learning. During this pandemic the educational institutions have been forced to adopt online learning without practicing it. As a consequence, there are several challenges to be encountered by the facilitator as well as learners to benefit from it. This paper is a descriptive study of e learning scenario among the learners of    higher education in commerce deanery. This paper aims at finding out the factors which lead to student’s active engagement in the online classes. 1065 students from various colleges who had attended online classes in the last six months responded through a structured questionnaire and the data was analyzed to find out the students’ understanding and learning.